Exercise Capacity and Mortality in Patients with Ischemic Left Ventricular Dysfunction Randomized to Coronary Artery Bypass Surgery or Medical Therapy: An Analysis From the Surgical Treatment for Ischemic Heart Failure (STICH) Trial - Stewart, Ralph (2014)
OBJECTIVE: To assess the prognostic significance of exercise capacity in patients with ischemic left ventricular (LV) dysfunction eligible for coronary artery bypass surgery (CABG). BACKGROUND: Poor exercise capacity is associated with mortality, but it is not known how this influences the benefits and risks of CABG compared to medical therapy. METHODS: In an exploratory analysis physical activity was assessed by questionnaire and 6-minute walk test in 1,212 patients before randomization to CABG (n=610) or medical management (n=602) in the STICH trial. Mortality (n=462) was compared by treatment allocation during 56 (IQR 48 to 68) months follow-up for subjects able (n=682) and unable (n=530) to walk 300m in 6 minutes and with less (Physical Ability Score >55, n= 749) and more (PAS ≤55, n=433) limitation by dyspnea or fatigue. RESULTS: Compared to medical therapy mortality was lower for patients randomized to CABG who walked ≥300m (HR 0.77, 95% CI 0.59 to 0.99, p=0.038) and those with a PAS >55 (HR 0.79, 95% CI 0.62 to 1.01, p=0.061). Patients unable to walk 300m or with a PAS ≤55 had higher mortality during the first 60 days with CABG (HR 3.24, 95% CI 1.64 to 6.83, p=0.002) and no significant benefit from CABG during total follow-up (HR 0.95, 95% CI 0.75 to 1.19, p=0.626, interaction p=0.167). CONCLUSION: These observations suggest that patients with ischemic LV dysfunction and poor exercise capacity have increased early risk, and similar 5 year mortality with CABG compared to medical therapy, while those with better exercise capacity have improved survival with CABG.